Relation between systematic risk and fundamental variables of the firm - Sıvacıyan, Talin A. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1985., 1985)
In this thesis the relationship e~isting between fundamental firm variables and the beta coefficient, which is the systematic risk measure. is studied: Capital asset pricing model is used for this analysis. 20 firms are taken as sample. And the sample time is chosen to be 10 years. First of all the beta coefficient of each firm is estimated via simple regression analysis. For this study the expected return rate of each firm. the market rate of return and ri sk free rates for ten years are calculated. The regression analysis has not given any reliable result therefore it is concluded that there is no correlation between the expected return of· the common stock and the market. This means that in Turkey the expected return does not fluctuate according to the market movement. Therefore the capital asset pricing model is not applicable. Not being able to estimate the value of beta coefficients leads us to set another hypothesis. It is tbought that the expected return of the common stock is directly related to the fundemental variables of the firms. The variations of the expected returns are dependent on the changes of the management policies. Relation between expected. return asset size ratio and the variables of the firm (such as liquidity. dividend payout asset size ratio, and earning variability asset growth ratio) is found. In spite of these resul ts, to reUe on these findjngs will be very optimistic in an economic envjronment where a capital market does not exist, where correct data are impossible to find, and where investors do not have any risk concept. With an unstable economjc envjronment, wjth an always changing industry characteristics and with djscontunjtjes of management policies it is impossible to base upon past data where the time lapis very large as 10 years and therefore it is not possjble to make future expectation.
Keywords: Risk management.; Capital assets pricing model.; Business enterprises -- Finance.